Analysis of Asphalt Concrete Highway Construction Technology in Highway Engineering - Zheng, Siyuan; Zhu, Jiaming; Wu, Yuanyuan; He, Jiarong (Journal of Theory and Practice of Engineering Science, 2023)
In recent years, asphalt concrete has been commonly used for construction in highway engineering in China. In actual construction, asphalt concrete construction technology has a serious impact on the quality of highway engineering. Therefore, in order to strictly control quality and effectively avoid safety accidents during highway engineering construction. This requires relevant personnel to strengthen the analysis and research of asphalt concrete road construction technology, in order to meet the latest requirements for the quality of concrete pavement construction in the context of rapid urbanization in China. The following article will analyze the construction technology of asphalt concrete engineering in highway engineering, hoping to have a certain effect on improving the quality of highway engineering construction in China.